The development of consensus-based pre-hospital core competencies and outcomes as a component of specialist emergency physician training - a South African-based study - Vlok, Neville (Emergency Unit, 2025)
BACKGROUND: South African Emergency Medicine registrars undertake between one and three-month pre-hospital work placements as a component of the specialist training programme. Anecdotally, the experiences of trainees nationally vary substantially which may be attributed to the lack of a curriculum to guide expected graduate outcomes, teaching, learning or assessment in Pre-Hospital Emergency Medicine (PHEM). Although efforts are underway to renew the EM curriculum in SA by the College of Emergency Medicine (CEM), this is the first body of research dedicated towards a pre-hospital curriculum for South African EM specialist training. AIM: To seek consensus on expected graduate level pre-hospital core competencies and generate broad learning outcomes for the SA EM specialist training curriculum. METHODS: A modified nominal group technique (NGT) was used to derive PHEM competencies and outcomes for specialist trainees. A scoping review of the literature informed the NGT by extrapolating global pre-hospital competencies and outcomes for registrars. Fourteen experts in either pre-hospital education and/or practice and specialist EM physicians were purposively recruited. A summary of core competencies and outcomes were presented to the panel over two virtual sessions. PHEM core competencies and broad-level outcomes were generated through consensus and context-specific gaps in the international literature were addressed and suggestions also presented for consensus. RESULTS The panel concluded that the WHO Emergency Care Systems Framework (ECSF) was appropriate to organise competencies and outcomes. The consensus process yielded 6 core competencies and 36 broad-level outcomes; eleven outcomes for scene response, 21 for transport and 4 for facility. CONCLUSION: The consensus process allowed researchers to design a curriculum framework for a PHEM module which can inform the specialist training curriculum for the CEM SA. Aviation for Health Care Provider and Hospital Major Incident Medical Management and Support courses potentially address specific outcomes. Self-directed and experiential learning have been highlighted as crucial teaching-learning methodologies, and opportunities identified for transprofessional collaboration. The results reported here could be used in the next steps of curriculum development.